Indeks Kepuasan Masyarakat Pada Pelayanan Dinas Koperasi Usaha Kecil Dan Menengah Kabupaten Bekasi - Hajiji, Merdi; Gunadi, Trida (Koaliansi : Cooperative Journal, 2022)
The Community Satisfaction Index (IKM) is data and information about the level of community satisfaction obtained from the results of quantitative and qualitative measurements of people's opinions in obtaining services from public service providers by comparing their expectations and needs. The results of the community satisfaction survey for the type of service at the Office of Cooperatives, Small and Medium Enterprises, Bekasi Regency show that the quality of service at the Office of Cooperatives, Small and Medium Enterprises has a satisfaction index of 79.02 and is categorized as a "good" service unit which is in the SKM between 76, 61 -  88.30.